The Effects of Health Belief Model and Trust in Media on Vaccination Behavior: Case Study of Generation Y and Z on Muslim Communities in City of Bekasi - Dewi Udhany; Benedictus A. Simangunsong (Budapest International Research and Critics University, 2022)
During the Covid-19 pandemic, vaccine hesitancy has been a major problem not only in the world but also in Indonesia. This makes it difficult for the Government of Indonesia to carry out the herd immunity against the Covid-19 virus. In this study, we want to investigate whether the health belief model (HBM) and trust in the media have a significant effect on Covid-19 vaccination behavior. We use a quantitative approach which is conducted by survey method. Generation Y and Z within Muslim communities in Bekasi City are the subject and locus of the research, respectively. We obtain the primary data by distributing questionnaires to 242 respondents through non-probability sampling technique. We found that three of the five dimensions of the Health Belief Model, namely: (1). perceived vulnerabilities; (2). perceived benefits; and (3). perceived barriers, had a significant effect on the behavior of the Covid-19 vaccination. Meanwhile, trust in the media, which includes trust in traditional media and new media, also has a significant effect on the Covid-19 vaccination behavior of generation Y and Z Muslim communities in Bekasi City.